2020
DOI: 10.1049/iet-rpg.2019.0589
|View full text |Cite
|
Sign up to set email alerts
|

Control and operation of a three‐phase local energy router for prosumers in a smart community

Abstract: From the electrical energy point of view, the smart community (SC) concept is meant to be as a sustainable and environmentally friendly alternative to the classical configuration. The SC includes small-scale renewable energy sources (RES) and small-scale energy storage system (ESS). The SC energy management system acts as an aggregator, aiming to assure benefits for community stakeholders. These trends led to the energy routers (ERs) concept. This study proposes and describes the control strategies for these E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 32 publications
0
9
0
Order By: Relevance
“…In this paper, an algorithm based on the perturb and observe (P&O) method with adaptive step to minimize the power fluctuation is implemented. Details of this method are available in [27]. Figure 5 represents a typical P-V curve where the maximum power point with coordinates (VMPP, PMPP) is marked.…”
Section: Pv Power Regulationmentioning
confidence: 99%
“…In this paper, an algorithm based on the perturb and observe (P&O) method with adaptive step to minimize the power fluctuation is implemented. Details of this method are available in [27]. Figure 5 represents a typical P-V curve where the maximum power point with coordinates (VMPP, PMPP) is marked.…”
Section: Pv Power Regulationmentioning
confidence: 99%
“…Carlos et al. [15] proposed an EER that can control active and reactive power, but the design is three‐phase, which is applied to smart community but is not suitable for home users. Sahar et al.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is necessary to design an EER for the intelligent management of household electricity. Carlos et al [15] proposed an EER that can control active and reactive power, but the design is three-phase, which is applied to smart community but is not suitable for home users. Sahar et al [16] studied the optimal scheduling of residential complex based on renewable energy under the real-time pricing mechanism.…”
Section: Introductionmentioning
confidence: 99%
“…Energy routers are regarded as the primary network units for implementing energy internet [3–5]; therefore, energy routers are expected to become core components of future microgrids and 5G BS power supply systems [6]. Previous research [7] has demonstrated the advantages of energy routers with a focus on traditional power grids, which cannot meet the needs of microgrids involving multiple distributed energy sources.…”
Section: Introductionmentioning
confidence: 99%